Wear testing of total hip replacements under severe conditions - Zietz, Carmen; Reinders, Jörn; Kretzer, Jan Philippe (Expert review of medical devices, 2015)
Controlled wear testing of total hip replacements in hip joint simulators is a well-established and powerful method, giving an extensive prediction of the long-term clinical performance. To understand the wear behavior of a bearing and its limits under in vivo conditions, testing scenarios should be designed as physiologically as possible. Currently, the ISO standard protocol 14242 is the most common preclinical testing procedure for total hip replacements, based on a simplified gait cycle for normal walking conditions. However, in recent years, wear patterns have increasingly been observed on retrievals that cannot be replicated by the current standard. The purpose of this study is to review the severe testing conditions that enable the generation of clinically relevant wear rates and phenomena. These conditions include changes in loading and activity, third-body wear, surface topography, edge wear and the role of aging of the bearing materials.